Perkembangan dan Kandungan Nutrisi Larva Hermetia illucens (Linnaeus) (Diptera: Stratiomyidae) pada Bungkil Kelapa Sawit - RACHMAWATI RACHMAWATI; DAMAYANTI BUCHORI; PURNAMA HIDAYAT; SAURIN HEM; MELTA R. FAHMI (Perhimpunan Entomologi Indonesia, 2010)
Hermetia illucens, is used as a reducing agent of palm kernel meal (PKM), as well as one of alternative protein sources for aquaculture purposes. Information about biology of H. illucens is absolutely required in mass production. The objectives of these researches were to study the development of H. illucens including the effect of supplementary food to the adult, and nutrient content of the immature stage. The sample of 20 larvae from each 3 replicates were measured and weighed on 0-19th day (larva) and 24th day (pupa) from egg hatching. H. illucens adults were fed by water and honey 5% (v/v). Eggs were collected and counted. Nutrient content of immature stage: 5, 10, 15, 20 days old (larvae), and 25 days old (prepupae) reared on PKM were analyzed proximately. Dry matter was determined by weight loss on drying at 105 oC during overnight. Crude protein was determined by Kjeldahl procedure (N x 6.25), crude fat by soxhlet (ether extract), crude ash by determining the residue after heating at 550 oC for 4–5 h. Data were analyzed descriptively by average from triplicate. The development of H. illucens was shorter than those in previous studies as the differences of abiotical factor. PKM was a suitable medium for development. It was better, however, to fed the adult with honey since it could enhance the fecundity. The young larva certainly contained the best quality of nutrition. To meet the quantity of mass production, however, the use of the elder larva (bigger) was suggested.